Sociodemographic Profile and Co-morbid Symptoms among Individuals with Semen Loss (Bangladesh Journal of Medicine, 2021)
Background: Semen loss and associated problems, sometimes known as ‘Dhat syndrome’ or ‘Semen loss anxiety’, are found specially in the cultures of South Asian region including Bangladesh. The aim of this study was to assess the physical, psychological and sexual problems in the patients complaining semen loss.Methods: This cross-sectional study was conducted at the outpatient department of National Institute of Mental Health, Dhaka, Bangladesh. All the male patients (aged 18-60 years) with self-reported complaints of semen loss were included in the study. Within three months, data were collected from 95 respondents through face to face interview with a semistructured questionnaire. Data analysis was performed using Statistical Package for Social Sciences (SPSS) version 24.Results: Mean age of the respondents was 23.7 (±5.1) years. Almost half (47.4%) of the respondents belonged to the age group of 21-30 years. Majority of them was Muslim (94.7%), married (54.7%), completed primary education (42.1%), currently unemployed (46.3%) and resided in urban area (87.4%), Most of the respondents complained of semen loss through urine (57.9%), followed by through night emission (18.9%) and masturbation (16.8%). All respondents complained more than one other symptom. Common physical symptoms were physical weakness (89.8%) and vertigo (50.5%), psychological symptoms were anxiety (49.8%) and depression (38.9%) and sexual symptoms were premature ejaculation (42.1%) and erectile dysfunction (31.6%).Conclusion: There were various other physical, psychological and sexual problems among the patients with the complaints of semen loss. So, other symptoms should be considered and managed when dealing with these patients.Bangladesh J Medicine July 2022; 33(1) : 64-69